Morphological, ethological and genomic discrimination of functional stocks of spotted grunter, an estuarine-dependent fish - Coetzee, Vivienne Nicole (Department of Biological Sciences, 2025)
This thesis investigates the differences between spotted grunter Pomadasys commersonnii from two biogeographically distinct South African estuaries, 800 km apart, and relates these differences to the environmental properties of these estuaries, in particular turbidity. Understanding both the phenotypic and genotypic mechanisms that structure spotted grunter populations is beneficial for their effective conservation and management, especially in the advent of climate change and anthropogenic pressures. The two study sites, the Breede Estuary and the Kei Estuary, represent low and high turbidity habitats, respectively. These properties affect the ability of fishes to use visual and acoustic modes of interaction. Moreover, recent literature has suggested the establishment of a recent divergent breeding population of spotted grunter in the Breede Estuary. Genetic and phenotypic differences, that drive population divergence, do not progress at the same rate and the divergence of these traits will occur at different timescales. This thesis provides a multifaceted approach that incorporates both phenotypic and genetic analyses of traits that can change over different timescales to identify any differences in fish originating from these two estuaries of contrasting turbidity. Consequently, four characteristics were chosen: (1) spot patterns, (2) otolith shape morphology, (3) acoustic repertoire and (4) genomic analysis. Markings and colouration of fishes are traits associated with camouflage as well as inter and intra-specific communication. As the species name implies, spotted grunter have distinct spot patterns. It was hypothesised that the spot patterns of spotted grunter living in turbid environments would differ from those living in less-turbid environments. It was important to establish the degree of phenotypic plasticity in spot patterns prior to field studies. Thus, a controlled aquarium experiment was conducted in order to ascertain the degree to which spotted grunter individuals can alter their spot pattern in response to changes in turbidity. The experiment revealed that an individual cannot alter the number or position of their spots but can adapt their spot size and brightness in response to changes in turbidity levels. Changes to spot size and brightness were also found to be reversible. Subsequent findings from the field revealed that spotted grunter from the less turbid Breede Estuary presented with more- and larger spots, for a given size range, compared to those living in the turbid Kei Estuary. Acoustic communication involves the dual process of generating and receiving sounds, where the functionality of the vocal organs must be paired with an appropriate sensory counterpart. Therefore, one would expect changes in the acoustic repertoire to coincide with changes in otolith morphology. Otoliths are under dual regulation by both genetic and environmental factors. It was hypothesised that (1) spotted grunter from the two biogeographically distinct estuaries would exhibit differences in their otolith morphology and (2) there would be differences in the otolith outlines of spotted grunter captured in the Breede Estuary pre-2002 and post-2019. While each otolith is unique to some degree, the results revealed significant differences in the outlines of otoliths from spotted grunter samples, both spatially and temporally. Furthermore, these differences could be used to assign individuals to their specific populations. As with most species of the Haemulidae family, spotted grunter produce rasping-or as the name suggests- ‘grunting' sounds, by stridulation of their pharyngeal teeth, which are amplified by the swim bladder. These sounds are species specific in terms of a number of acoustic properties. With respect to turbidity, it was hypothesised that the acoustic properties of voicings or vocalisations of spotted grunter from turbid environments would differ from those in less turbid environments. The findings from the field experiment confirmed this hypothesis, albeit in a manner opposite to expectations. Individuals from the less -turbid Breede Estuary produced longer, louder sounds of a lower frequency; this is presumed to be due to differences in each estuary's ambient noise or due to spotted grunter communication behaviour whereby acoustic signals may only succeed visual signals. The divergence of phenotypic stocks can eventually alter the genomic structure of a species. Despite differences in the phenotypic characters measured above, the genomic results suggested a single panmictic population of spotted grunter. Interestingly, a few highly differentiated loci were identified and some of these loci were associated with the measured phenotypic characteristics. Therefore, despite evidence for high gene flow occurring between these two estuaries, the highly differentiated loci may suggest early stages of divergence. This research marked the initial discovery that functional stocks of spotted grunter differ in aspects related to sound production, colouration and pattern. Currently, these differences are temporary, reversible phenotypic adaptations to local environments. However, if a new breeding population is established in a different biogeographic zone with unique environmental properties these differences could result in a genetically, morphologically and ethologically distinct population of spotted grunter, with distinct conservation and management requirements.